2022
DOI: 10.3390/medicina58070879
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Patterns of Traditional Chinese Medicine for Ischemic Heart Disease Treatment: A Population-Based Cohort Study

Abstract: Background and objectives: Traditional Chinese medicines (TCMs) are widely prescribed to relieve ischemic heart disease (IHD); however, no cohort studies have been conducted on the use of TCMs for patients with IHD. The aim of the study was to analyze TCM prescription patterns for patients with IHD. Materials and Methods: The retrospective population-based study employed a randomly sampled cohort of 4317 subjects who visited TCM clinics. Data were obtained from the National Health Insurance Research Database (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Its precise mechanism of action is not fully understood, but it is believed to improve blood flow, reduce inflammation, protect against oxidative stress, and inhibit platelet aggregation. It is commonly used for angina, coronary artery disease, and myocardial infarction [ 34 ]. Xiao-Juan et al performed a randomized clinical trial comparing the ABC group to the ABCD group among subjects undergoing coronary angioplasty for unstable angina.…”
Section: Relevant Clinical Trials That Have Used Non-traditional Ther...mentioning
confidence: 99%
“…Its precise mechanism of action is not fully understood, but it is believed to improve blood flow, reduce inflammation, protect against oxidative stress, and inhibit platelet aggregation. It is commonly used for angina, coronary artery disease, and myocardial infarction [ 34 ]. Xiao-Juan et al performed a randomized clinical trial comparing the ABC group to the ABCD group among subjects undergoing coronary angioplasty for unstable angina.…”
Section: Relevant Clinical Trials That Have Used Non-traditional Ther...mentioning
confidence: 99%
“…Salvia miltiorrhiza , a herb renowned for its traditional use in treating cardiovascular diseases like coronary heart disease, atherosclerosis, myocardial infarction, and angina pectoris, belongs to the class of herbs known to stimulate blood circulation and alleviate blood stasis ( Wang et al, 2022 ). Notably, a study demonstrated that post-ischemic reperfusion recovery in left ventricular developed pressure was significantly improved, and contracture was reduced in hearts treated with Salvia miltiorrhiza compared to untreated hearts ( Zhou and Ruigrok, 1990 ).…”
Section: Introductionmentioning
confidence: 99%